HUMAN RESISTANCE TO THE USE OF INFORMATION TECHNOLOGY IN CONSTRUCTION COMPANIES - Andi Andi; Fani Fani; Heru Purwoadi (Institute of Research and Community Outreach - Petra Christian University, 2005)
The process of implementing information technology (IT) often fails to bring the intended result because the human dimension is not given adequate consideration. Yet despite some evidence of failure, little has been written on the nature of human performance, compared to abundant resources about technical and procedural aspects, as it applies to the ideals of the IT philosophy. To combat peopleâs deficiencies, this paper focuses mainly on the question why people resist IT. It explores sources of human resistance to the use of IT. A survey is the conducted to personnel working for construction companies to examine the resistance sources. The result reveals personal money, habit, and threat to information security as most dominant sources for such resistance, instead of fear of employment instability as many previous researches have discussed. The paper discusses the resistances and suggests possible solutions to deal with them.